Conquista Inka y paisajes rituales en los Nevados de Cachi, Noroeste Argentino - Leibowicz, Ivan Federico (2022)
This paper describes an astronomical and landscape analysis at four Inca sites located in the Nevados de Cachi, North Calchaquí Valley, in the Province of Salta, Argentina. In particular, we considered existing ushnu platforms and their associated architectural elements, such as gnomons, and a petroglyph in Guitian, Cortaderas, El Apunao, and Uña Tambo. These results show the location, spatial layout, and arrangement of particular structures within Inca settlements based on astronomical orientations involving solstices, equinoxes, and lunar standstills